Thermal state of permafrost and active-layer monitoring in the antarctic: advances during the international polar year 2007-2009 - Vieira, Goncalo (2010)
Results obtained during the International Polar Year (IPY) on the thermal state of permafrost and the active layer in the Antarctic are presented, forming part of ANTPAS (‘Antarctic Permafrost and Soils’), which was one of the key projects developed by the International Permafrost Association and the Scientific Committee for Antarctic Research for the IPY. The number of boreholes for permafrost and active-layer monitoring was increased from 21 to 73 during the IPY, while CALM-S sites to monitor the active layer were increased from 18 to 28. Permafrost temperatures during the IPY were slightly below 08C in the South Shetlands near sea-level, showing that this area is near the climatic boundary of permafrost and has the highest sensitivity to climate change in the region. Permafrost temperatures were much lower in continental Antarctica: from the coast to the interior and with increasing elevation they ranged between 13.38C and 18.68C in Northern Victoria Land, from 17.48C to 22.58C in the McMurdo Dry Valleys, and down to 23.68C at high elevation on Mount Fleming (Ross Island). Other monitored regions in continental Antarctica also showed cold permafrost: Queen Maud Land exhibited values down to 17.88C on nunataks, while in Novolazarevskaya (Schirmacher Oasis) at 80 m a.s.l. the permafrost temperature was 8.38C. The coastal stations of Molodeznaya at Enderby Land showed permafrost temperatures of 9.88C, Larsemann Hills – Progress Station in the Vestfold Hills region – recorded 8.58C, and Russkaya in Marie Byrd Land, 10.48C. This snapshot obtained during the IPY shows that the range of ground temperatures in the Antarctic is greater than in the Arctic.